Pulsed Plasma X-ray and EUV Sources - C.S, Wong, (Malaysian Journal of Science, 2002)
Recently, the development of pulsed plasma devices as X-ray and EUV sources for applications in nanolithography and microscopy has been the research topic in many laboratories around the world. In this paper, we review the research effort on three types of pulsed plasma sources being carried out in this laboratory. The devices reviewed are the plasma focus and the vacuum spark as X-ray sources; and the pulsed capillary discharge as EUV source.